The Analysis Of Refusal Speech Act In Some Selected Episodes In “Friends” Drama Series - Ade Mulyadi (Syntax Literate, 2019)
The study aims to known what are types of refusal speech act and dominant refusal in some selected episodes in Friends drama series, In this research the writer employs the qualitative research. The writer had divide into 5 steps. First, the writer watchesof Friend‟s video. Second, the writer reads of Friend‟s script. Third, the writer givesa mark of refusal speech act on the script of “Friends” drama series. Fourth, the writer grouped the type of refusal speech act. And the last, the writer analyzed the classifying of type of refusal speech act and dominant type of the refusal speech act in communication used by all character of some selected episodes in Friends drama series. Based on the data analysis, it can be concluded that, this research the writer find seven types of refusal according to Turnbull and Saxton (1997:145-181), use ofmodality used by some selected episodes in “Friends” drama series with three episodes, those are: episodes: 1: The One Where Monica Gets a New Roommate, episode 2: The One with the Sonogram at the End, episode 3: The One with theThumb. They are: Negate request (35%), Use performatives (3%), Indicate reluctance (15%), Indicate Impediments (1 1%), Avoid decision (7%), Show goodwill (19%) and Suggest alternative (10%).Key Word: Refusal, types of Refusal, Dominant type of Refusal.